Щодо резильєнтності суб’єктів ринку на прикладі підприємств добувної галузі - Amosha, Oleksandr I.; Cherevatskyi, Danylo Yu.; Bash, Vitalii O. (Institute of Industrial Economics of NAS of Ukraine, 2023)
The last period (starting with the pandemic) cataclysms determined the importance for the macro- and microeconomies resilience as the ability of ecosystems, business, society to cope with shocks and continue to function in approximately the same way.The topic of resilience is extremely important for mining companies, because they cannot afford any relocation and industrial repurposing.The goal of this work is to clarify the essence of resilience and identify the factors that determine it for subjects of the market system.Research methods: general scientific – abstraction, analysis, synthesis, observation, generalization; the microcosm-system approach, which is an extension of the world-system approach to microeconomics; cumulative cost curves; single-factor production functions; methods of mathematical and statistical analysis; Zipf-Pareto law.The base of observations is the global coking coal market, production and economic indicators of the Ukrainian iron ore mining company.It is shown that the unprofitability of industrial and commercial activity is a necessary but not sufficient condition for the microcosm-economy to lose resilience. The loss of resilience is a process whose active actors, along with the direct subjects of the market, are their owners, the state and other subjects and authorities. The final stage of resilience loss occurs after the market subject crosses a certain point of no return.A model of a certain market is a cumulative cost curve. The final part of the cumulative cost curve`s graph, where the elements with the worst economic characteristics (high-risk group) are located, is significantly non-linear. The rank of the element position on the curve mathematically determines with the Zipf-Pareto law the cost value and identify the zone of market entities profitable functioning according with the market price of products.The application of the logit-regression model makes it possible to estimate the probability of a market subject's profitability loss at its inherent cost and the confidence interval of prices observed during a certain period.The risk degree of resilience loss is determined not only by the factors of the market itself, but also by the production function characteristic of the subject of market activity. The article provides an example of a one-factor logarithmic production function of a Ukrainian iron ore mining company.